Laos - Stads, Gert-Jan; Vongsipasom, Phonepaseuth; Omot, Norah; Pham, Nguyen Thi; Nin-Pratt, Alejandro; Bouahom, Bounthong (International Food Policy Research Institute, 2019)
Agricultural R&D capacity in Laos has risen steadily over time, but R&D expenditures have exhibited an erratic trend in recent years. In 2017, the country invested only 0.26 percent of its AgGDP in agricultural research.